Promoting Self-Control through Reflective and Participatory Emotional Training: A Macro-Level Intervention for Adolescent Girls in An Orphanage - Fitri, Rindifa Amilatul; Aulia, Ranisya Wilda; Karyani, Usmi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aimed to enhance self-control among children at Aisyiyah Girls Orphanage in Grogol, Sukoharjo using modul intervention "Strengthening Self-Control in Children Through Emotion Training." The subjects of this intervention were 28 female children residing at the orphanage. The intervention was carried out using a macro-level approach, employing methods such as observation, semi-structured interviews, and participatory training. The training was conducted on June 11, 2025, over a span of 2 hours and 15 minutes, and consisted of four sessions: (1) Know Yourself, Know Your Friends, (2) When Emotions Arise, What Should I Do?, (3) Choose Your Path, Take Responsibility, and (4) Building a Healthy Group. Evaluation was conducted through follow-up interviews with the orphanage caregiver. The results revealed positive changes in the children's social dynamics, such as increased empathy, healthier communication, and the establishment of collective agreements, including borrowing with permission and advising without belittling. These values have begun to be internalized and practiced in the children's daily lives. The training proved effective in fostering self-control and creating a more emotionally supportive and healthy environment within the orphanage.